Influenza‐like illness‐related emergency department visits: Christmas and New Year holiday peaks and relationships with laboratory‐confirmed respiratory virus detections, Edmonton, Alberta, 2004–2014. Issue 1 (30th August 2016) - Martin, Leah J.; Im, Cindy; Dong, Huiru; Lee, Bonita E.; Talbot, James; Meurer, David P.; Mukhi, Shamir N.; Drews, Steven J.; Yasui, Yutaka
Abstract : Background: Emergency department (ED) visit volumes can be especially high during the Christmas–New Year holidays, a period occurring during the influenza season in Canada. Methods: Using daily data, we examined the relationship between ED visits for the chief complaint "cough" (for Edmonton, Alberta residents) and laboratory detections for influenza A and respiratory syncytial virus (RSV) (for Edmonton and surrounding areas), lagged 0–5 days ahead, for non‐pandemic years (2004–2008 and 2010–2014) using multivariable linear regression adjusting for temporal variables. We defined these cough‐related visits as influenza‐like illness (ILI)‐related ED visits and, for 2004–2014, compared Christmas–New Year holiday (December 24–January 3) and non‐holiday volumes during the influenza season (October–April). Results: Adjusting for temporal variables, ILI‐related ED visits were significantly associated with laboratory detections for influenza A and RSV. During non‐pandemic years, the highest peak in ILI‐related visit volumes always occurred during the holidays. The median number of holiday ILI‐related visits/day (42.5) was almost twice the non‐holiday median (24) and was even higher in 2012–2013 (80) and 2013–2014 (86). Holiday ILI‐related ED visit volumes/100 000 population ranged from 56.0 (2010–2011) to 117.4 (2012–2013). In contrast, lower visit volumes occurred during the holidays of pandemic‐affected years (2008–2010). Conclusions: During non‐pandemic years, ILI‐related ED visit volumes were associated with variations in detections for influenza A and RSV and always peaked during the Christmas–New Year holidays. This predictability should be used to prepare for, and possibly prevent, this increase in healthcare use; however, interventions beyond disease prevention strategies are likely needed.